Variations en C: Espèces de que dans l’espace gallo-roman - Anne Dagnac (Studii de Lingvistica)
The aim of this paper is empirical: it presents the geographical span of the so-called Doubly Filled Comp constructions in Gallo-romance dialects in the Atlas Linguistique de la France, i.e. constructions where an instance of que is followed by a WHphrase. The contexts under review are root WH-questions, free and bounded relative clauses, embedded exclamative clauses in comment ‘how’ and temporal clauses in quand ‘when’. Three local varieties of que are also examined: que following si ‘if’ in conditional clauses; the so-called Gascon enunciative particle; and doubled que in a Picard dialect. The geographical distribution of these various instances of que turns out to be largely restricted to (though not exclusive of) the Oïl area, though each construction may exhibit a different span.